(untitled) (Research, Society and Development, 2025)
Schizophrenia is a chronic psychotic disorder, of multifactorial origin, involving genetic and environmental factors. The concept emerged at the end of the 19th century with Emil Kraepelin, who called it "dementia praecox". Later, Bleuler introduced the term "schizophrenia", emphasizing the division between emotions and behavior. Historically, treatment was primitive, with violent practices such as trepanation and lobotomy. The change began with Leo Navratil, who realized the relationship between art and schizophrenia, encouraging artistic expression. In Brazil, the 8th National Health Conference (1986) boosted psychiatric reform, promoting deinstitutionalization and creating Psychosocial Care Centers (CAPS). Art began to be seen as a therapeutic tool, contributing to the humanization of treatment and health professionals. The objective of this study is to present the research project that adopts a narrative approach to analyze paintings that portray schizophrenics, taking into account artistic, anatomical, semiological and cultural aspects. The analysis was based on articles from platforms such as Scielo, Google Scholar and PubMed. The research discusses how painting can be a form of expression for schizophrenic individuals, especially due to the negative symptoms of the disease, such as difficulty communicating. Analysis of the works of artists such as Edvard Munch, Richard Dadd and August Natterer reveals how their paintings reflect typical symptoms of schizophrenia. It is concluded that art is an important tool for understanding schizophrenia and can help humanize medical care, highlighting the importance of arts in medical education.